Formins: linking cytoskeleton and endomembranes in plant cells - Cvrčková, Fatima; Oulehlová, Denisa; Žárský, Viktor (International journal of molecular sciences, 2014)
The cytoskeleton plays a central part in spatial organization of the plant cytoplasm, including the endomebrane system. However, the mechanisms involved are so far only partially understood. Formins (FH2 proteins), a family of evolutionarily conserved proteins sharing the FH2 domain whose dimer can nucleate actin, mediate the co-ordination between actin and microtubule cytoskeletons in multiple eukaryotic lineages including plants. Moreover, some plant formins contain transmembrane domains and participate in anchoring cytoskeletal structures to the plasmalemma, and possibly to other membranes. Direct or indirect membrane association is well documented even for some fungal and metazoan formins lacking membrane insertion motifs, and FH2 proteins have been shown to associate with endomembranes and modulate their dynamics in both fungi and metazoans. Here we summarize the available evidence suggesting that formins participate in membrane trafficking and endomembrane, especially ER, organization also in plants. We propose that, despite some methodological pitfalls inherent to in vivo studies based on (over)expression of truncated and/or tagged proteins, formins are beginning to emerge as candidates for the so far somewhat elusive link between the plant cytoskeleton and the endomembrane system.
Keywords: proteiny buněčného cyklu; Protein Binding; transport proteinů; proteiny huseníčku; Intracellular Membranes; Plant Cells; intracelulární membrány; Actin Cytoskeleton; Arabidopsis Proteins; Cell Cycle Proteins; Protein Transport; mikrofilamenta; proteiny asociované s mikrotubuly; Microtubule-Associated Proteins; vazba proteinů; rostlinné buňky